A discrete isodiametric result: The Erdős–Ko–Rado theorem for multisets. (August 2015) - Füredi, Zoltán; Gerbner, Dániel; Vizer, Máté
Abstract: There are many generalizations of the Erdős–Ko–Rado theorem. Here the new results (and problems) concern families of t -intersecting k -element multisets of an n -set. We point out connections to coding theory and geometry. We verify the conjecture that for n ≥ t ( k − t ) + 2 such a family can have at most ( n + k − t − 1 k − t ) members.